Caregivers’ perceptions of childhood fever in Ilorin, North-Central Nigeria - Abdulkadir MB; Johnson WBR (Nigerian Journal of Paediatrics, 2024)
Background: Fever remains a common clinical indicator of disease, accounting alone for over 25% of paediatric emergency rooms consultations. Perception of this important sign is a crucial prelude and determinant of outcome in febrile children. The aim was to determine knowledge and attitudes of parents regarding fever in their children.